Effectiveness of prime vendor system on availability of medicines and medical supplies in the selected public health facilities in Arusha district council - Liberatus Elias; Lawrencia Mushi (BMC Health Services Research, 2024)
Abstract Introduction The shortage of medicines and medical supplies remains to be a major issue that is facing public health facilities in Tanzania. This situation has been influenced by lack of consistency in the supply chain, increase in healthcare demand, poor regulatory system, insufficient funds, and lack of conducive infrastructure. Formerly, the Government initiatives such as engagement with the Prime Vendor System (PVS) demonstrated great assistance in getting rid of this challenge. Despite the operation of PVS, a recent shortage of medicines and medical supplies has been noticed. Objectives This study aimed to assess the effectiveness of PVS on the availability of medicine and medical supplies in the selected public health facilities in Arusha District Council. Methods The study used a case study design with mixed research approach. The study involved 77 respondents which included 25 health facility in-charges, 50 patients, 1 District Pharmacist and 1 Prime Vendor. Questionnaires, interviews, and observation methods were used to collect data. Data collected covered a period of 2021–2022. Thematic analysis was used to analyze the qualitative data whereas descriptive analysis was used to analyze the quantitative data with the help of Excel and the Statistical Package for Social Sciences (SPSS) version 28.0. Results The analysis indicates that PVS is not completely effective in supplying medicines and medical supplies due to its low capacity to conform to the orders placed by the public health facilities, a lack of supply competition, and a failure to adhere to contractual terms. Furthermore, at the time of data collection, the average availability of medicines and medical supplies at the selected public health facilities was 74.8%, while 80% of the selected public health facilities reported having a scarcity of medicines and medical supplies, and 92% of the interviewed patients reported having no full access to medicines. Conclusion Despite the shortcomings associated with the operation of the PVS, the system still seems to be very important for enhancing the availability of medicines and medical supplies once its effectiveness is strengthened. This study recommends a routine monitoring of PVS operations and timely interventions to reinforce an adherence to the contracted terms and improve PVS effectiveness.